Normative reference interval for youths on the Difficulties in Emotion Regulation Scale (DERS) - Thoustrup Christine Lykke; Olsen Markus Harboe (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology)
The Difficulties in Emotion Regulation Scale (DERS) is widely used in both clinical and non-clinical research to assess emotional regulation difficulties. To guide interpretation of scores, establishing thresholds for normative DERS scores is informative. However, despite its widespread use, to date no study has provided such threshold for youths. This literature review aimed to fill this gap by examining the 90% reference interval for the DERS in youths aged 11–19 years.